›Grundlinien zum Systeme der Aesthetik‹ (1824) und andere kunstphilosophische Schriften - Heiberg, Johan Ludvig (Kierkegaard Studies. Monograph Series, 2022)
Alongside an edition of his manuscript "Elements of the Systems of Aesthetics" (1824), written in German, this volume brings together a number of first translations of the most important aesthetic writings by the Danish philosopher Johan Ludvig Heiberg (1791-1860). An introduction presents Heiberg's philosophy. His texts played a key role in the history of Danish Hegelianism and had great significance for Søren Kierkegaard.